Impacted Lower First Molar and Labial Ectopic Upper Canine Eruption in an Individual from the Prehistoric American Southwest - Greg C. Nelson (Dental Anthropology Association, 2010)
Tooth impactions and other positional anomalies are commonly encountered in clinical situations but are much less frequently seen in, or reported from, prehistoric archaeologically derived contexts. This report examines the occurrence of two positional anomalies, lower first molar impaction and upper canine labial ectopic eruption, in a single individual from the Ancestral Pueblo Gallina Phase (1100-1275 AD) of northern New Mexico. Although outwardly dissimilar, appearing as they do in different tooth classes and both the mandible and maxilla, their underlying similarity implies a common etiology. The co-occurrence of these anomalies presents an opportunity to explore the etiological basis of positional anomalies and possibly provide some insight into the very early stages of dental morphogenesis.